Análisis e Interpretación a los Estados Financieros de la Cooperativa de Ahorro y Crédito GlobalCoop de la Ciudad de Loja, Períodos 2014-2015. Propuesta De Mejoramiento - Valladolid González, Mabel del Cisne (2017)
The thesis work entitled "Analysis and Interpretation of the Financial Statements of the GlobalCoop Savings and Credit Cooperative of the City of Loja, Periods 2014 - 2015. Proposal for Improvement" was done based on the objectives set forth, That in order to comply with them, we proceeded to collect the necessary documentation in order to prepare the vertical analysis of the financial statements, which establishes the financial structure and the participation of the equivalent percentages to each account that intervene in the Economic and financial position of the cooperative, with its respective graphical representation and interpretation, in addition the horizontal analysis was carried out in which the financial movements and the variations are established, being these increases or decreases of the figures in the financial statements included in the period Of study 2014-2015. Subsequently, the indicators established by the regulatory body (SEPS) were applied, through which the economic and financial activity of the cooperative, Capital, Asset Quality, Microeconomic Efficiency, and Profitability, Intermediation and Efficiency Financial, its level of Liquidity and Vulnerability of the Heritage. Finally, the final, easy-to-understand report for managers and managers, in which the results of the analysis and situation of the cooperative were presented, is prepared and argued. 6 Finally, the proposal for improvement was elaborated, which is aimed at proposing alternatives for improvement that lead to increase profitability levels and thus to achieve the permanence of the cooperative in the financial market, these alternatives are embodied in a Financial Analysis report , To serve as a guide to the company's partners in decision-making. Likewise, the conclusions are presented with their respective recommendations, which are based on the results obtained, from which it is established that the cooperative has not carried out any financial analysis, which has not allowed to know its true economic and financial position. After analyzing the data presented in the Financial Statements, it is highlighted that the decisions taken by the managers and administrators of the GlobalCoop Credit Union regarding the granting and placement of credits are carried out without a thorough analysis of the capacity Economic growth of clients, which is causing high levels of delinquency in the credit portfolio and therefore a decrease in the surplus of the cooperative, therefore it is suggested that the credit policies of the cooperative be improved and that the credit department perform the Activities for monitoring, control and efficiency in the placement and recovery of resources in an efficient manner, since the respective analysis is not being carried out in terms of granting of credits, in order to avoid that the cooperative maintains a high level in the portfolio bad.